Analisis Implementasi Metode Home Visit di Masa Pandemi Covid-19 dalam Mengatasi Masalah Belajar Siswa pada Mata Pelajaran Matematika Materi Pecahan Kelas IV SDN Batursari 6 Mranggen Demak - Larasati, Reka; Purnamasari, Iin; Basyar, Mohammad Aniq Khairul (CV. Supernova Office Stationary and Printing, 2022)
This study was to find out the reasons for choosing the home visit method, how the process of implementing the home visit method was, how the response of parents and students to the implementation of the home visit method to overcome student learning problems in the mathematics subject matter of fractions in class IV SDN Batursari 6 Mranggen Demak. This type of research is qualitative research. The research population is class IV SDN Batursari 6 Mranggen Demak. The research subjects were all students of class IVB at SDN Batursari 6 Mranggen Demak for the academic year 2021/2022. The data in this study were obtained through teacher and principal interview instruments, observation sheets, parent and student questionnaires, and documentation. The implementation of home visits can be an effort to overcome student learning difficulties because teachers can know firsthand the condition of the learning environment and the development of each student.